Implementasi Media Pembelajaran E-Book Berbasis Kvisoft Flipbook Maker terhadap Hasil Belajar IPA Ditinjau dari Gender Peserta Didik - Nur Mughny Hadi; Muhammad Tawil; Muhammad Aqil Rusli (Universitas Negeri Makassar, 2023)
This research aims to determine: (1) High learning outcomes of students in class VIII SMPN 24 Makassar before using Kvisoft flipbook maker-based E-book learning media, (2) High learning outcomes of students in class VIII SMPN 24 Makassar after using Kvisoft flipbook maker-based E-book learning media, and (3) Differences in learning outcomes between male and female students in class VIII SMPN 24 Makassar. This research is a pre-experiment with One Group Pretest Posttest Design. The population was all students of class VIII SMPN 24 Makassar, the sample was selected using purposive sampling technique so that 2 classes were selected with a total of 45 students. The instruments in this research are Pretest and Posttest tests in the form of multiple choice questions. Data analysis techniques are descriptive and inferential. The results of the research found: (1) The learning outcomes of students in class VIII SMPN 24 Makassar before using Kvisoft flipbook maker-based E-book learning media have an average overall score of 36.71 including in the low category, (2) The learning outcomes of students in class VIII SMPN 24 Makassar after using Kvisoft flipbook maker-based E-book learning media have an average overall score of 61.24 including in the medium category (3) There are differences in learning outcomes between male and female students after using Kvisoft flipbook maker-based E-book learning media.